Ações de patrocínio no setor público: uma análise sobre terminologias, conceitos e entendimentos da gestão cultural no Brasil - Cabral, Melissa de A. (2012)
This work tackles issues regarding cultural sponsorship in Brazil, focusing, particularly, on the ones in the public sector, in the ambit of media actions. It is a research of the themes that are involved in the elaboration, management and (bureaucratic) processes of a sponsorship project, through the contributory prism that can help reflect on questions related to the meaning of specific terminology and concepts which are used in this area. The result of this work aims at becoming a source of information that can stimulate reflection on cultural sponsorship in the public sector, specifically regarding issues of terminology and concepts, in a field that still lacks established standard parameters in relation to its language and the understanding of management processes. In the conclusive part of the dissertation, a glossary of sponsorship expressions is presented to work as a source of memory regarding names and meanings that are important.